The influence of brand image, location and price on purchasing decisions of Dunkin' Donuts products - Ryu Antony Yakin; Basar Maringan Hutauruk (Institute of Computer Science (IOCS), 2023)
Intense competition in the food industry certainly affects the level of consumer purchasing decisions. Decisions for consumers about a product or service go through a series of processes and methods from brand information, opinions on how other brands are able to meet consumer needs and until they can determine the chosen brand. Companies must also be able to determine a strategic location that is easy for consumers to reach, which is close to the city center or activity center and determine reasonable prices in order to attract consumers to buy products. This study aims to determine the effect of brand image, location and price on purchasing decisions of Dunkin' Donuts partially and simultaneously. This study uses a quantitative approach. Data collection used questionnaire data and literature study with a population of Pelita Bangsa University students who had bought Dunkin' Donuts. Sampling used a non-probability sampling method with a purposive sampling technique with a total sample of 100 respondents, namely Pelita Bangsa University students who had bought Dunkin' Donuts. This study uses SPSS software. Data analysis was carried out by conducting validity test, reliability test, classic assumption test, multiple linear analysis and hypothesis testing. The results of the study state that brand image has no effect on purchasing decisions. Location has a positive and significant effect on purchasing decisions. Price has no effect on purchasing decisions. And brand image, location and price simultaneously influence purchasing decisions.